PENERAPAN POLA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PERANGKAT DESA TEMENGGUNGAN KECAMATAN KREJENGAN KABUPATEN PROBOLINGGO - Sudarwis; Gunadi; Djuni Farhan (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2022)
Employee performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. Factors that affect performance are leadership patterns and work discipline. Based on this, this research study aims to determine the application of leadership patterns, and work discipline to the performance of village officials in Temenggungan Village, Krejengan District, Probolinggo Regency. The aims of this study were: (1) To determine the application of the leadership of the Temenggungan village head, Krejengan District, Probolinggo Regency in forming work discipline on device performance. (2) To find out the obstacles in forming work discipline for village officials in the village of Temenggungan, Krejengan District, Probolinggo Regency. (3) To find out the efforts made in the efforts made in solving the problem of establishing work discipline on the performance of village officials in the village of Temenggungan, Krejengan District, Probolinggo Regency. This study uses a qualitative method. Qualitative research is a scientific research, which aims to understand a phenomenon in a natural social context by prioritizing the process of deep communication interaction between researchers and the phenomenon under study. Researchers took the research location with observations in Temenggungan Village, Krejengan District, Probolinggo Regency to support the data needed in research related to the implementation of the internal communication bureaucratic reform program in supporting the implementation of organizational change management. Sources of data obtained from the field where the research was carried out. To obtain this data, the interview method was used. This data was obtained from the results of the answers of related informants.